Facile synthesis of unique cellulose triacetate based flexible and high performance gel polymer electrolyte for lithium ion batteries - Nirmale, Trupti C.; Karbhal, Indrapal; Kalubarme, Ramchandra S.; Shelke, Manjusha V.; Varma, Anjani J.; Kale, Bharat B. (ACS Applied Materials & Interfaces, 2017)
Lithium ion batteries (LIBs) with polymer based electrolytes have attracted enormous attention due to the possibility of fabricating intrinsically safer and flexible devices. However, economical and eco-friendly sustainable technology is an oncoming challenge to fulfill the ever increasing demand. To circumvent this issue, we have developed a gel polymer electrolyte (GPE) based on renewable polymers like cellulose triacetate and poly (polyethylene glycol methacrylate) p(PEGMA) using a photo polymerization technique. Cellulose triacetate offers good mechanical strength with improved ionic conductivity, owing to its ether and carbonyl functional groups. It is observed that the presence of an open network has a critical impact on lithium ion transport. At room temperature, GPE PC exhibits an optimal ionic conductivity of 1.8 x 10(-3) S cm(-1) and transference number of 0.7. Interestingly, it affords an excellent electrochemical stability window up to 5.0 V vs Li/Li+. GPE PC shows a discharge capacity of 164 mAhg(-1) after the first cycle when evaluated in a Li/GPE/LiFePO4 cell at 0.5 C-rate. Interfacial compatibility of GPE PC with lithium metal improves the overall cycling performance. This system provides a guiding principle toward a future renewable and flexible electrolyte design for flexible LIBs (FLIBs).